CORRELAÇÃO DE FATORES INTRAOPERATÓRIOS EM CIRURGIA DE REVASCULARIZAÇÃO DO MIOCARDIO - Steinke, Angela; Dallazen, Fernanda; Windmöller, Pollyana; Cruz, Dante T. d.; Winkelmann, Eliane R. (Salão do Conhecimento, 2013)
Resumo